2005
DOI: 10.1142/s0218127405012429
|View full text |Cite
|
Sign up to set email alerts
|

Model Reduction for Fluids, Using Balanced Proper Orthogonal Decomposition

Abstract: Many of the tools of dynamical systems and control theory have gone largely unused for fluids, because the governing equations are so dynamically complex, both high-dimensional and nonlinear. Model reduction involves finding low-dimensional models that approximate the full high-dimensional dynamics. This paper compares three different methods of model reduction: proper orthogonal decomposition (POD), balanced truncation, and a method called balanced POD. Balanced truncation produces better reduced-order models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
516
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 805 publications
(518 citation statements)
references
References 16 publications
2
516
0
Order By: Relevance
“…The proper orthogonal decomposition (POD) method and variants of POD are commonly used, but they can miss important flow physics [31]. The balanced POD method introduced by Rowley [32] can be better than POD in control applications, but it requires an adjoint solution to be computed, which makes the method unsuitable for experimental data. Ma et al [33] showed that the eigensystem realization algorithm [34] method obtained the same models as balanced POD, but an adjoint was not required.…”
Section: B Eigensystem Realization Algorithm and Observer/kalman Filmentioning
confidence: 99%
“…The proper orthogonal decomposition (POD) method and variants of POD are commonly used, but they can miss important flow physics [31]. The balanced POD method introduced by Rowley [32] can be better than POD in control applications, but it requires an adjoint solution to be computed, which makes the method unsuitable for experimental data. Ma et al [33] showed that the eigensystem realization algorithm [34] method obtained the same models as balanced POD, but an adjoint was not required.…”
Section: B Eigensystem Realization Algorithm and Observer/kalman Filmentioning
confidence: 99%
“…In the context of this work we only detail the specific choices performed in relation to the problem at hand, for more details about POD applied to fluid problems we address the reader to e.g., Rowley [29] and Willcox and Peraire [30].…”
Section: Proper Orthogonal Decompositionmentioning
confidence: 99%
“…For this reason, reduced-order models based on proper orthogonal decomposition (POD) modes alone may require additional modes to reproduce important dynamics [151]. A reduced-order model can instead be formed by projecting the system operator onto the first few direct and adjoint-balanced truncation modes [152]. Balanced truncation modes are similar to POD modes in that they may be computed through a snapshot method.…”
Section: (A) Trends In Hpc: Towards Exascale Computingmentioning
confidence: 99%